2012
DOI: 10.1002/anie.201203190
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels Incorporating GdDOTA: Towards Highly Efficient Dual T1/T2 MRI Contrast Agents

Abstract: Do not tumble dry: Gadolinium-DOTA encapsulated into polysaccharide nanoparticles (GdDOTA NPs) exhibited high relaxivity (r(1) =101.7 s(-1) mM(-1) per Gd(3+) ion at 37 °C and 20 MHz). This high relaxation rate is due to efficient Gd loading, reduced tumbling of the Gd complex, and the hydrogel nature of the nanoparticles. The efficacy of the nanoparticles as a T(1)/T(2) dual-mode contrast agent was studied in C6 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
144
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 26 publications
(2 reference statements)
7
144
0
Order By: Relevance
“…Compared to other strategies based on bioconjugation or encapsulation 6 , models made on the optimization of “rigidification” 7 and “confinement” 8 of metal chelates seem to be the most effective at enhancing the effect of GBCAs without the chemical modification of the chelate 9 . Recently, we have also explored the impact in the bulk of cross-linked and uncross-linked biopolymer matrices on relaxometric properties of CAs.…”
mentioning
confidence: 94%
“…Compared to other strategies based on bioconjugation or encapsulation 6 , models made on the optimization of “rigidification” 7 and “confinement” 8 of metal chelates seem to be the most effective at enhancing the effect of GBCAs without the chemical modification of the chelate 9 . Recently, we have also explored the impact in the bulk of cross-linked and uncross-linked biopolymer matrices on relaxometric properties of CAs.…”
mentioning
confidence: 94%
“…In the first report [23] related to hydrogel nanoparticles, the improvement in the relaxivity was attributed by the authors to both the restriction of the rotational motion of the gadolinium complex and the highly hydrated nature of the hydrogel network, which enhances the outer-sphere water molecule interactions and effectively transfers magnetic effect to the bulk water. This previous principle was also used to explain the higher 2 relaxivity of polyamide dendrimers with HOPO [24,25], where the outer-sphere water exchange plays a large role in 2 relaxation.…”
Section: D3mentioning
confidence: 99%
“…In the literature, some research has been reported about simultaneous increases in both relaxivity constants 1 and 2 This was accomplished either by entrapping DOTAREM in hydrogel nanoparticles [23] or by outfitting polyamide dendrimers with hydroxypyridinone (HOPO) complexes [24,25]. In the first report [23] related to hydrogel nanoparticles, the improvement in the relaxivity was attributed by the authors to both the restriction of the rotational motion of the gadolinium complex and the highly hydrated nature of the hydrogel network, which enhances the outer-sphere water molecule interactions and effectively transfers magnetic effect to the bulk water.…”
Section: D3mentioning
confidence: 99%
“…Courant et al . enhanced relaxivity by encapsulating Gd-chelates (Gd-DOTA) into hydrophilic and biocompatible polymer nanoparticles (about 250 nm) obtained by the ionotropic gelation between Chitosan (CH) and Hyaluronic Acid (HA)24.…”
mentioning
confidence: 99%